Assessment Of Quality And Maturity Of Green Waste Compost In Algeria - ANNAB, Souheila; Bouadam, Roukia (Journal of Architecture and environment of child, 2024)
Currently, Algeria’s environment and economic policies prioritise the implementation of circular economy ideas. The execution of these programmes mostly relies on the advancement of trash recycling and composting. This article aims to examine the sustainable management of green waste by means of composting. The objective is to evaluate the calibre and level of development of compost derived from green waste and to demonstrate that composting may serve as a sustainable substitute for incinerating green waste in Algeria. The approach relies on empirical investigation. A pilot initiative has been established at the El Khroub commune nursery to collect waste from pruning and weeding activities in green spaces. The purpose of this project is to make compost, which is a completely natural fertiliser. The physico-chemical investigations validate that the compost possesses favourable characteristics and is abundant in organic matter, rendering it appropriate for agricultural use. Furthermore, a germination test conducted with radishes yielded a germination rate of 97%, indicating that the compost is fully mature and poses no phytotoxicity or harm to plants. The research findings indicate that the effectiveness of composting is directly correlated with the rate at which the raw materials decompose and, most importantly, with the quality of the final output. The maturity of compost is a crucial criterion to consider and monitor to assess the quality of compost as a soil amendment.